Pengaruh Permainan Bola Voli Mini Terhadap Peningkatan Kebugaran Jasmani Pecandu Narkoba - Rismaningtyas, Kurnia (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
This study aims to answer the following questions: 1) the influence of a volleyball mini-gamemodel to increase physical fitness of drug addicts in prisons Women Class II A Semarang in2015. 2) How big contribution volleyball mini model of the game due to the improvement ofphysical fitness of drug addicts in prisons Women Class II A Semarang in 2015. . T test resultsobtained tcount for data post test of 2,420 with significance 0.022 <0.05, which means thatthe average physical fitness between the experimental and control groups after treatment wassignificantly different. Judging from an average of 35.79 in the experimental group and thecontrol group of 32.92 indicates that the level of physical fitness of women prisoners IIA classdrug addict treatment Semarang made a game of volleyball mini-game is better than that donot follow the game of volleyball mini , In the experimental group increased physical fitnesssignificantly, evident from the value t = 6.541 with a significance value of 0.000 <0.05. It wasconcluded that: 1) Model mini volleyball games that do can improve the physical fitness of inmatesin prisons Women Class II A Semarang. 2) In the experimental group showed that themodel of a volleyball mini-game has a significant influence on the improvement of physicalfitness on female inmates in prison Women drug addicts Class II A Semarang.